Characterization of tannery wastewater and its treatment by aquatic macrophytes and algae - Jahan, MAA; Akhtar, N; Khan, NMS; Roy, CK; Islam, R; Nurunnabi, M (Bangladesh Journal of Scientific and Industrial Research, 2015)
Tannery wastewater contains large amount of chemical compounds including toxic substances. So an attempt was made to characterize physiochemical parameters of tannery wastewater and investigate the efficacy, and applicability of the biological treatment utilizing aquatic plants macrophytes and algae. Total suspended solids TSS and total Dissolved solid in the original wastewater were found 1250 mg/l and 21300 mg/l respectively. The pH and temperature were 8.3 and 29°C. Dissolved Oxygen (DO), Biological Oxygen Demand (BOD) and Chemical Oxygen Demand (COD) were 2.72 mg/l, 4464 mg/l and 12840 mg/l respectively. Electrical conductivity (EC) was 42500 ?S/cm anions PO43- and Cl- were 17.1 mg/l and 13.8 mg/l respectively. Heavy metals were also analysed. Fe, Na, Zn, Cr, Pb and Ca were found 14.675 mg/l, 12006 mg/l, 1.5241 mg/l, 10.348 mg/l, 0.1818 mg/l and 0.4112 mg/l respectively. Biological treatment with aquatic plants, algae and their combination treatments were found to be effective for the reduction of some physiochemical parameters. Treatment conducted with Eichhornia crassipes was found most effective in reducing COD, EC, TDS and TSS. Mixed treatment resulted reduction of pH from 8.3 to 6.21. Both macrophytes and algae exhibited good heavy metal uptake tendency, but Eichhornia crassips was identified as most effective for the removal of heavy metals in the wastewater because of its extensive root system which provides to help the uptake of pollutants from the wastewater. DOI: http://dx.doi.org/10.3329/bjsir.v49i4.22626 Bangladesh J. Sci. Ind. Res. 49(4), 233-242, 2014